Desain Website UMKM “Kedai Buah dan Oleh-oleh Dayat” Menggunakan Template Website dan Blogger - Saputri, Anggela; Roy Bin Yulius; Syarifah Nur (CV. ITTC INDONESIA, 2024)
In the digital era, having a website has become a crucial need for Micro, Small, and Medium Enterprises (MSMEs) to enhance visibility and competitiveness. This research aims to explore the process of creating a website for the MSME